Associated injuries are common among patients with bicycle-related craniofacial fractures - Puolakkainen, Tero; Murros, Olli-Jussi; Abio, Anne; Thorén, Hanna; Virtanen, Kaisa; Snäll, Johanna (Journal of oral and maxillofacial surgery, 2021)
Purpose - Ample evidence exists on the relationship between bicycle injuries and craniofacial fractures. However, as the mechanism behind these injuries is often multifactorial, the presence of associated injuries (AIs) in this study population requires further examination. We hypothesized that patients with craniofacial fracture injured in bicycle accidents are at high risk of sustaining severe AIs, especially those of the head and neck region. - Patients and Methods - The investigators performed a retrospective study on all patients with bicycle-related craniofacial fracture admitted to a tertiary trauma centre during 2013 to 2018. The predictor variable was defined as any type of craniofacial fracture. The outcome variable was defined as any kind of AI. Other study variables included demographic and injury-related parameters. Variables were analyzed using bivariate and Firth's logistic regression analyses. - Results - A total of 407 patients were included in the analysis. Our results revealed that AIs were present in 150 (36.9%) patients; there were multiple AIs in 47 cases. Traumatic brain injuries followed by upper limb injuries were the most frequent AIs. Severe head and neck injuries were present in 20.1% of all patients with craniofacial fracture. AIs were observed in 57.4% of patients with combined midfacial fractures (P < .001). Helmet use had a protective effect against traumatic brain injuries (P < .001). - Conclusions - Our results suggest that AIs are relatively common in this specific patient population. Close co-operation in multidisciplinary trauma centers allowing comprehensive evaluation and treatment can be recommended for patients with bicycle-related craniofacial fracture.
Gesehen am 05.08.2021